Aspek Aksiologis Pendidikan Dalam Novel Laskar Pelangi Karya Andrea Hirata - Rosmiati, Ana (Pendhapa, 2009)
Education is the most important thing in life. An Indonesian person of good quality will only be obtained with education. Andrea Hirata, the author ofLaskar Pelangi, explored the problems of education which made reader be fascinated. Andrea told real facts and imagination into a beautifully flowing story. The composition containing the integration of plot, characterizing, theme, and setting is thought to be very good. The language flows beautifully. Andrea told the condition of SD Muhammadiyah with its very alarming facilities. This condition is much different from that of SDPenambangan timah which has complete utilities and facilities. The difference of the two schools is obvious. Key words : Value, Education